Role of Bridge Contraception in Postpartum Long-Acting Reversible Contraception and Sterilization Fulfillment Rates. Issue 3 (September 2018) - Montague, Mary; Ascha, Mustafa; Wilkinson, Barbara; Verbus, Emily; Morris, Jane; Mercer, Brian M.; Arora, Kavita Shah
Abstract : OBJECTIVE: To estimate the association of bridge contraception with interval long-acting reversible contraception (LARC) and sterilization fulfillment rates. METHODS: This is a secondary analysis of a retrospective single-center cohort chart review study examining 1, 851 postpartum women who requested LARC or sterilization after discharge. Bridge contraception was requested by 597 of these women. Primary outcomes included LARC or sterilization fulfillment, time to fulfillment, postpartum visit attendance, and pregnancy within 365 days of delivery. RESULTS: The rate of LARC or sterilization fulfillment within 90 days of delivery was 147 of 597 (24.6%) women using bridge contraception and 287 of 1, 254 (22.9%) women not using bridge contraception ( P =.41). After adjusting for maternal age, parity, gestational age, mode of delivery, adequacy of prenatal care, race–ethnicity, and education level, the use of bridge contraception was associated with LARC or sterilization fulfillment (adjusted odds ratio [OR] 1.30, 95% CI 1.02–1.67). Adequacy of prenatal care and black race was associated with fulfillment. The use of bridge contraception was not associated with time to fulfillment (adjusted hazard ratio 1.17, 95% CI 0.95–1.44) or postpartum visit attendance (adjusted OR 0.97, 95% CI 0.77–1.23). The use of bridge contraception was not associated with increased pregnancy within 365 days of delivery (OR 1.00, 95% CI 0.95–1.05; adjusted OR 0.96, 95% CI 0.73–1.26). CONCLUSION: Bridge contraception is associated with increased LARC and sterilization fulfillment after postpartum discharge. Long-acting reversible contraception or sterilization fulfillment after discharge occurred in less than one in four women. Strategies to improve provision of LARC or sterilization before hospital discharge are necessary. Abstract : Postpartum bridge contraception is associated with increased long-acting reversible contraception and sterilization fulfillment after hospital discharge.